The Oxford Handbook of International Investment Law 2012
DOI: 10.1093/oxfordhb/9780199231386.013.0009
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of Taxation Under Modern Investment Treaties

Abstract: This chapter provides an overview of the regulation of taxation in modern investment treaties and the underlying policies and tensions reflected in the variations of treaty regulation of tax disputes. Section 1 sets the scene for the discussion, placing tax-related investment disputes in the political and economic context. It argues that under the current regulatory state, in which the function of the state has retreated from that of controlling the ‘commanding heights’ of the economy to regulation, the tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…28 In many cases, they bring certain benefits to the host state, including greater tax revenue, creation of employment opportunities and skills development, scientific development, transfer of new technologies, and sound management practices through linkages with local firms. 29 In the environmental context, it is observed that the prosperity brought by FDI enables the pursuit of 'higher societal expectations for environmental quality of life', 30 and technological advancement and good practices brought by TNCs may contribute to better environmental protection in the host state. 31 In the human rights context, it is also argued that TNCs, in particular consumer product firms that are concerned with the cost of negative publicity and consumer protests, can be 'a powerful lever for improving local human rights conditions'.…”
Section: Environmental and Human Rights Impact Of Tnc Activitiesmentioning
confidence: 99%
“…28 In many cases, they bring certain benefits to the host state, including greater tax revenue, creation of employment opportunities and skills development, scientific development, transfer of new technologies, and sound management practices through linkages with local firms. 29 In the environmental context, it is observed that the prosperity brought by FDI enables the pursuit of 'higher societal expectations for environmental quality of life', 30 and technological advancement and good practices brought by TNCs may contribute to better environmental protection in the host state. 31 In the human rights context, it is also argued that TNCs, in particular consumer product firms that are concerned with the cost of negative publicity and consumer protests, can be 'a powerful lever for improving local human rights conditions'.…”
Section: Environmental and Human Rights Impact Of Tnc Activitiesmentioning
confidence: 99%
“…Muchos tratados establecen limitaciones específicas para la aplicación de ciertas garantías, o incluso de todo el tratado, a controversias sobre o relacionadas con materia tributaria (Wälde y Kolo, 2008). En inglés, se denominan como cláusulas de carve-out.…”
Section: A Excepciones En Materia Tributariaunclassified
“…Debe tenerse en cuenta, no obstante, que es común encontrar limitaciones a la aplicación de este estándar en materias tributarias. Por ejemplo, en el caso Occidental contra Ecuador (2004) el tribunal interpretó el BIT Estados Unidos-Ecuador y la limitación de materias tributarias únicamente para casos de expropiación, protección a las transferencias y acuerdos de inversión (Wälde y Kolo, 2008).…”
Section: Trato Justo Y Equitativounclassified
“…Such provisions governing the interaction of these regimes attempt to prevent normal international tax issues from being decided in other forums, but they are not completely excluded. There is a long history of state actions directed at foreign investors taking the form of taxation measures, which have been treated as indirect expropriation, and some argue that this has become a more acute problem with the expansion of the regulatory state (Wälde and Kolo 2008). In addition, the very broad nature of the non-discrimination provisions in investment agreements can create opportunities for legal arguments that may be unexpected, unless specific exclusions are inserted.…”
Section: The Interaction With International Trade and Investmentmentioning
confidence: 99%
“…Hence, some tax-related cases have been brought under investment agreements. They especially concern claims of discriminatory or retroactive taxation, and windfall or capital gains taxes particularly in extractive industries (Wälde and Kolo 2008;Sidhu 2014;Transnational Institute 2016). The most egregious example has been the long-running dispute concerning the seizure by Russia of the Yukos Oil Corporation, allegedly for tax evasion.…”
mentioning
confidence: 99%